Understanding the participation of breast screening among women born in predominantly Muslim countries living in Victoria, Australia from record-linkage data. - Tahira Yeasmeen; Margaret Kelaher; Julia M L Brotherton; Michael J Malloy (PLoS ONE, 2020)
Background Early detection of breast cancer can improve survival rates and decrease mortality rates. This study investigates whether there are significant differences in participation in breast screening among women born in Muslim countries compared to women born in Non-Muslim countries and Australia. Methods Screening data from January 1st, 2000 to December 31st, 2013 from the Breast Screen Victoria Registry (BSV) was linked with hospital records from the Victorian Admitted Episodes Dataset (VAED). Countries having more than 50% of their population as Muslim were categorised as Muslim countries. Age adjusted rates were calculated for women born in Muslim and Non-Muslim countries and compared with the Australian age adjusted rates. Logistic regression assessed the association between screening status and other factors which include country of birth, marital status, age and socio-economic status. Results Women born in Muslim countries (Odds Ratio (OR) = 0.70, 95%CI = 0.68-0.72) and in other Non-Muslim countries (OR = 0.87, 95%CI = 0.86-0.88) had lower odds of participation in breast screening than Australian born women. Women aged 60-64 years (OR = 1.42, 95%CI = 1.40-1.44) had higher odds of participation in the BreastScreen program than 50-54 age group. Conclusion This study provides valuable insights to understanding breast screening participation among women born in Muslim countries residing in Victoria. This population level study contributes to the broader knowledge of screening participation of women born in Muslim countries, an understudied population group in Australia and across the world. This study has implications for breast screening programs as it highlights the need for culturally sensitive approaches to support breast screening participation among women born in Muslim countries.